(untitled) (Colombia Medica, 2006)
Objective: To determine the effect of the periodical use of the prenatal biopsychosocial risk assessment (PBR) to predict obstetric and perinatal complications in pregnant women in Asian countries. Materials and methods: In Shanghai, China, and Dhaka, Bangladesh, 565 healthy primigravids were evaluated with PBR at inclusion (14-27 weeks), in a second time (28-32 weeks) and in a third time (33-42 weeks) with assessment of the perinatal outcome. Results: The average age was 25.1±6.4 years old. Most of the women were from middle socioeconomic level, with university academic degree and urban residence. There were 129 (25.6%) obstetric complications, 54 (10.1%) low birth weight babies and 41 (7.3%) perinatal deaths. The ROC analysis showed that the high PBR score was associated with obstetric complications (area under ROC Curves) 0.80 CI 95% 0.71-0.89, preterm birth (area under ROC curves) 0.79, CI 95% 0.68-0.90, low birth weight (area under ROC curves) 0.85, CI 95% 0.77-0.93. The best predictive period was the last (33-42 weeks) to obstetric complications (sensibility: 84.4%, specificity: 69.3%), preterm delivery (sensibility 79.2%, specificity 67.1%) and to low birth weight (sensibility 88%, specificity 77.3%). The baseline sociodemographic and nutritional characteristics and the perinatal outcome were different between the countries, however, the predictive effect of the instrument was similar. Conclusion: The prenatal biopsychosocial risk assessment was clinically valid to predict obstetric complications, preterm birth and low birth weight in two Asian countries when compared to results in Latin-American countries.